Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acsami.2c08019
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a LiF-Rich and Stable SEI Film by Designing a Binary, Ion-, and Electron-Conducting Buffer Interface on the Si Surface

Abstract: Stabilizing a solid electrolyte interface (SEI) film on the Si surface is a prerequisite for realizing silicon (Si) anode applications. Interfacial engineering is one of the effective strategies to construct stable SEI films on Si surfaces and improve the electrochemical performance of the Si anodes. This work develops a silver (Ag)-decorated mucic acid (MA) buffer interface on the Si surface and the obtained Si@MA*Ag anode retains 1567 mAh g −1 after 500 cycles at 2.1 A g −1 and exhibits 1740 mAh g −1 at 126 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 53 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…This implies that the SEI layer formed on the surface of the Si anode is composed of organic species at the outer compartment and inorganic species close to Si, as generally observed for other Si-based anodes. 44,45 Interestingly, the oxygen (O) content is obviously lower for the SE-based cell, particularly after sputtering, e.g., 36.3% (SE) vs 46.1% (RE) before sputtering and 38% (SE) vs 54.8% (RE) after sputtering for 240 s. This indicates that the decompositions of the carbonate solvent are significantly suppressed by the addition of elemental sulfur, considering that other components (e.g., LiPF 6 and Si) are free from oxygen-related moieties. Furthermore, the fluorine (F) content is significantly higher for the SE electrolyte [e.g., 47.3% (SE) vs 35.1% (RE) before sputtering], suggesting the presence of fluorine-rich components (e.g., LiF; cf.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This implies that the SEI layer formed on the surface of the Si anode is composed of organic species at the outer compartment and inorganic species close to Si, as generally observed for other Si-based anodes. 44,45 Interestingly, the oxygen (O) content is obviously lower for the SE-based cell, particularly after sputtering, e.g., 36.3% (SE) vs 46.1% (RE) before sputtering and 38% (SE) vs 54.8% (RE) after sputtering for 240 s. This indicates that the decompositions of the carbonate solvent are significantly suppressed by the addition of elemental sulfur, considering that other components (e.g., LiPF 6 and Si) are free from oxygen-related moieties. Furthermore, the fluorine (F) content is significantly higher for the SE electrolyte [e.g., 47.3% (SE) vs 35.1% (RE) before sputtering], suggesting the presence of fluorine-rich components (e.g., LiF; cf.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Notably, this exchange reaction does not require thermal activation and can occur once the electrolyte preparation is completed. The reduction reaction mechanism of the P­(BTMSB)­F 4 1– monoanion involves single electron transfer to accept electron and combine Li + to form inorganic lithium salt (LiF), which is beneficial to the stabilization of the SEI film. , Moreover, the inorganic components within the SEI film possess superior properties in terms of Li + transport compared to organic components. This can be attributed to the tendency of the inorganic SEI substance to bond Li + in ionic bonds that facilitates hopping-type transport mechanisms .…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have reported the effect of adding Ag nanoparticles (NPs) or AgNWs to improve charge carrier mobility and conductivity with a Si based anode. To date, porous Si/AgNPs/C, SiO 2 mixed with AgNPs, carbon paper coated with AgNPs, Si@SiOx/AgNP composite electrode, Si electrode mixed with nitrogen-doped carbon and Ps, Si particles with a buffer layer, and AgNPs in a core–shell form have been used as anode materials. By applying wire-type Cu and Ag, electron conduction can be induced in line contact with carbon in point contact, which creates a more effective conductive network than other alternatives.…”
Section: Introductionmentioning
confidence: 99%